Lincoln : a president for the ages - Weber, Karl, 1953- (Public Affairs, 2012)
" Lincoln, in theaters November 9, portrays America's 16th president when he faced two colossal challenges: winning the Civil War, and passing the Thirteenth Amendment, outlawing slavery and making permanent the promise of the Emancipation Proclamation. The politics of wartime, which required unity at all costs, conflicted with divisiveness of slavery. The president had to be at once true to his ideals and employ old-fashioned political cunning to outwit his rivals. This companion book, featuring a foreword by screenwriter Tony Kushner, invites historians and Lincoln experts to imagine Lincoln in eras other than his own, facing challenges of those times. How would Lincoln have handled the Second World War, or the politics of Civil Rights era, or the modern Republican Party? Using the character of Lincoln presented in the film - a man of high principle and low cunning - the book shows how Lincoln, a president for the ages, might indeed have taken America forward during other historic moments of drama and opportunity. "--